Histological assessment of regenerative endodontic treatment in animal studies with different scaffolds: A systematic review. Issue 4 (20th April 2017) - Altaii, Milad; Richards, Lindsay; Rossi‐Fedele, Giampiero
Abstract: Background/aim: The concept of regenerative endodontic procedures remains controversial. The aim of this study was to evaluate the histology of the tissues formed in immature animal teeth with necrotic and infected pulps after attempted endodontic regeneration procedures using different scaffolds. Design: A systematic electronic literature search was performed in PubMed, Web of Science, Scopus, EMBASE, DOSS, and Cochrane Library databases. The terms used were a combination of the following: "immature permanent necrotic tooth or teeth" or "open apex or apices" and "regeneration or revitalization or revascularization" and "histology." The inclusion criteria comprised animal studies with histological examination following regenerative endodontics in immature necrotic‐infected permanent teeth. Results: From 123 screened studies, 13 met the inclusion criteria. Formation of dentin‐like tissue on the dentinal walls was reported in only 4% of teeth treated with blood clot scaffold and 2% treated with blood clot with additional materials. Cementum‐like hard tissue was found in 64% of teeth with blood clot, 80% treated with blood clot with additional materials, 50% treated with alternative scaffolds, and 5% that were left empty. Bone‐like tissue was reported in 10% of teeth treated with blood clot, 2% treated with blood clot with additional materials, and 4% treated with alternative scaffolds. The tissues in the canal space were found to be connective tissue with infiltration of fibroblast‐like cells and blood vessels. Forty‐six percent of the studies reported formation of periodontal ligament‐like tissues. Conclusions: None of the regeneration protocols resulted in the predictable formation of a true pulp‐dentin complex.